Measuring Financial Well Being of Tourism Labor in Bali: A Comparative Study of Generation Z and Millennial - P, Wayan Agung Panca; Suasih, Ni Nyoman Reni; Yasa, I Gusti Wayan Murjana; Dewi, Made Heny Urmila (E-Journal of Tourism; Volume 11 Number 2 (September 2024), 2024)
Tourism in Bali is a hallmark of economic prosperity, attracting millions of tourists every year due to its natural beauty, rich cultural heritage, and preserved cultural heritage. Behind this vibrant industry are millions of labors whose livelihoods depend directly or indirectly on tourism. The research explores the financial well-being of the Millennial Generation (Generation Y) and Generation Z labors in the Bali tourism sector. This method uses a quantitative approach with crosstab analysis facilitated by SPSS Statistics 25, which was collected via questionnaires from 151 tourism labors in Bali.  The main findings show that although levels of financial well-being vary between generations, most respondents said they were happy with their finances. In addition, income disparities are visible, with the higher the age of tourism labors in Bali, the higher their income. However, regarding perception, financial well-being is relative, whereas generational age does not always influence financial well-being.  This research contributes to a deeper understanding of the dynamics of financial well-being among Bali tourism labors. The results of this research are expected to create strategies to increase income stability, job security, and financial literacy, which are recommended to support the tourism sector sustainably and improve the overall welfare of labors in Bali.